Electrophoretical Protein Profile in Apis mellifera (Hymenoptera; Apidae) Hypopharyngeal Glands under Juvenile Hormone Effect When the Colony is Grown in the Absence of Brood - Fioretti Gracioli, Luciana [UNESP]; Brochetto Brag, Márcia Regina [UNESP]; Silva de Moraes, Regina Lúcia Morelli [UNESP] (My University, 2003)
Twelve-day-old and 25-day-old Apis mellifera workers were treated or not treated with juvenile hormone at the moment of emergence and reared in the colony without brood. Having the brood interference apart, the hormone effect on the hypopharyngeal glands protein expression was determined through the electrophoretical protein profiles of the both groups of bees. In those conditions, the hormone induced changes that were different from the control. Protein bands of 66 and 48 kDa were intensified in the 12-day-old bees, whereas band of 42 kDa was reduced in the 25-day-old bees. That indicated a different effect of the juvenile hormone in the function of bee aging, which promoted a glandular protein activation in the young bees and, in contrast, an inhibitory action in the 25-day-old bees workers.
Keywords: Apis mellifera; Brood; Electrophoresis; Hypopharyngeal glands; Juvenile hormone; Apidae; Apoidea; Hymenoptera